2012
DOI: 10.1186/1556-276x-7-583
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid-stabilized non-spherical gold nanofluids synthesized using a one-step method

Abstract: Ionic liquid (IL)-stabilized non-spherical gold nanofluids have been synthesized by a one-step method in aqueous solution. The whole reaction proceeded in room temperature. In the presence of amino-functionalized ionic liquids, gold nanofluids with long-wave surface plasmon resonance (SPR) absorption (>600 nm) could be obtained by adopting tannic acid as the reductant. The specific SPR absorption was related to the non-spherical gold nanoparticles including gold triangle, decahedra, and icosahedra nanocrystals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Mouchet et al reported that a high mortality rate (85%) was noted at the highest double walled carbon nanotubes concentration against the larvae of Xenopus laevis [18] . Recent studies demonstrated that silver nanoparticles induce embryonic injuries and reduce survivals in zebrafish [19][20][21][22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…Mouchet et al reported that a high mortality rate (85%) was noted at the highest double walled carbon nanotubes concentration against the larvae of Xenopus laevis [18] . Recent studies demonstrated that silver nanoparticles induce embryonic injuries and reduce survivals in zebrafish [19][20][21][22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…The selection of the appropriate DHB@MNP dispersant was critical to avoiding the aggregation of nanoparticles to achieve a homogeneous coating of the nanomatrix onto the TLC plate. Ionic liquids have various unique properties and great chemical diversity finding application as a direct MALDI matrix , and suitable dispersion media for metal, silica, and gold nanoparticles. At first, we tested two common classes of ionic liquids (imidazolium and ammonium base) , for dispersion of our nanomatrix.…”
Section: Resultsmentioning
confidence: 99%
“…Functionalized IL"s are found very effective when used in conjunction with polymers and ligands exploring strategies involving electrostatic, steric and coordination along with electron donating ligands as discussed earlier. Various aspects of applying IL"s in metal NP stabilization have been reviewed in detail elsewhere providing more information [143,169,170].…”
Section: Surface Stability -Metal Npsmentioning
confidence: 99%